Consonance - dissonance between ratings of teachers and their application as perceived by students - Miljánovich Castilla, Manuel (2003)
When comparing the valuations from a sample that San Marcos' professors formulate about the university's substantial aspects with the students' perception of its application in educational practice, a high consonance degree is verified around the values related with democracy ( the respect to the human person, the cultivate of dialogue, the search of the truth in the scientific and humanistic investigation ) and an appreciable dissonance regarding the political and social values of social, pedagogic and ethical moral, of social, pedagogic and the ethical-moral projection. There are no variations according the careers that the students selected. The dissonance degree in the first years of studies is increasing in the last years, with some variations according to the values fields and careers.